Analysis of Heat Transfer in Vehicle Engine Cooling Systems Using Radiators with Fin Variations - Sayid Bahri Sriwijaya; Tika Kristianti (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research discusses heat transfer analysis in vehicle engine cooling systems, especially in radiators that use fin variations. The main objective is to compare the performance of several fin designs, including straight, zigzag, corrugated, and louvered, in terms of heat transfer efficiency and pressure loss. The research method adopted was a comparative study through secondary data collection from previous experimental results and numerical simulation (CFD). Quantitative descriptive analysis was used to compare key parameters such as inlet-outlet temperature difference (?T), heat transfer rate, and pressure drop. The study results show that the louvered and corrugated designs have the highest heat transfer rates, especially at medium to high air and fluid flow velocities. However, the improved thermal performance is accompanied by increased pressure loss, which requires adjustments to the fan and cooling pump capacity. The zigzag design offers a good compromise between cooling efficiency and increased mechanical load, while the straight fin tends to produce the lowest cooling efficiency, but with the lowest pressure loss.The practical implication of this study is the importance of considering the balance between increased cooling efficiency and the operational power requirements of the cooling system. Proper fin design selection can improve engine temperature stability, reduce the risk of overheat, and extend the life of engine components. In addition, the development of high thermal conductivity radiator materials and the production of more precise fins also determine the performance and service life of the radiator. Thus, the results of this research are expected to serve as a reference for the automotive industry in selecting and designing optimal vehicle radiators